Midnight flash model of energetic neutral atom periodicities at Saturn. Issue 7 (3rd July 2017) - Carbary, J. F.; Mitchell, D. G.
Abstract: The Ion Neutral Camera on the Cassini spacecraft made images of energetic H atoms (25–55 keV) over a 3 day span in 2017. The images were projected onto the equatorial plane of Saturn, and a keogram was made by interpolating the projections in local time at 9 R S (1 R S = 60268 km). The keogram intensities show strong periodicities near the 10.79 h period of Saturn's energetic particles and exhibit a slope commensurate with corotation at that period. These periodic fluxes intensify near midnight but are weaker near noon. A "midnight flash" model can explain this behavior in terms of a searchlight rotating at 10.79 h that intensifies in the midnight sector. The model can also describe similar activity in Saturn's kilometric radiation and magnetic fields, although the "flash" must be shifted to the dawn‐to‐noon sector. Key Points: Hydrogen ENA fluxes at 9 R S display a period near Saturn's 10.8 h period, and they also intensify near midnight A "midnight flash" model explains this behavior in terms of a rotating searchlight that intensifies in the midnight sector A "dawn flash" version of the model may also explain SKR and magnetic field periodicities Plain Language Summary: Saturn's magnetospheric periodicities have been viewed as either rotating source or a flashing source, and the two disparate ideas can be reconciled by a rotating source that intensifies as it rotates through a certain local time sector. In the case of energetic neutral atoms, the rotating source intensities or "flashes" at midnight.